KINERJA REKSA DANA PASAR UANG DENGAN METODE SHARPE, TREYNOR DAN JENSEN PADA BURSA EFEK INDONESIA (BEI) – PERIODE 2013 – 2017 - Budhi Suparningsih (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This study aims to determine the performance of money market mutual funds using the Sharpe, Treynor and Jensen methods for 5 years from 2013 to 2017. This research uses qualitative quantitative design. The selected money market mutual fund products are 5 aggressive money market mutual fund products, where the asset allocation is money assets. Data analysis method uses Sharpe, Treynor and Jensen methods. In general, the performance of money market mutual funds based on the Sharpe, Treynor and Jensen methods has fluctuated. The higher the value of Sharpe, Treynor and Jensen, the better the performance of the Money Market mutual fund, because it can provide actual return that is higher than the expected return so as to minimize the individual risk that it bears. Mutual funds with Sharpe and Jensen approaches, the best performance of money market mutual funds is PT Bahana Dana Likuid. Whereas according to Treynor’s approach the best is Danamas Rupiah Plus because for five years it gives a positive value. This shows that it is useful to provide information to investors who want to invest in Money Market Mutual Funds, because it results in a higher return on risk-free investment.